THE PERSPECTIVE TECHNOLOGIES OF IDENTIFICATION AND AUTHENTICATION OF FINANCIAL TRANSACTIONS - Golovashych, Sergiy (International Journal of Computing, 2014)
In the article comparative description of modern technologies of authentication on the basis of smart cards is presented, the lacks of each of the considered technologies are noticed and the chart of dynamic authentication which allows removing the basic exposed failing is offered. The ground of expedience of NFC-technology application for construction of authentication systems, providing maximal defense of user from abuses of attendants is shown also.